PENGARUH HARGA JUAL DAN SALURAN DISTRIBUSI TERHADAP VOLUME PENJUALAN PADA PERUSAHAAN DODOL NENAS DI KECAMATAN JALAN CAGAK KABUPATEN SUBANG - Mellisa, - (2009)
This Research is done upon 15 companies, researcher target is entrepreneur as determinant of selling price and distribution channel. This research is to know how big the relation between independent variable that is selling price ( X1) and distribution channel ( X2). While variable dependen is sale volume ( Y). Based on research type, that is analytic descriptive. Survey is done by taking sampel and using quetioner as compiler of data. Analysis technique that used are Simple Linear Regression, and Chi-Square. Based on result of statistical calculation, correlation coefficient of Product Moment between selling price variable ( X1) and sale volume ( Y) equal to 0,151. Chi-Square between distribution channel variable ( X2) and sale volume variable ( Y) equal to 7,557 which measured from distribution channel form and 5,519 which measured from marketing area target. While the result of Kontingensi Coefficient test is equal to 0,579 which measured from distribution channel form and 0,519 which measured from marketing area target. Therefore, writer suggest the company shall revise sell pricing method and election of using distribution channel, and also company able to determine methods and also more precise election for selling price and distribution channel so that sale volume will be more increasing.